Evaluation of seat and non-seat post preparation design using conventional and computational methods - G. Subrata; Z. Hasratiningsih; E. Kurnikasari; T. Dirgantara (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2009)
Background: Design of root canal preparation especially in cervical-third area of the root, is one of many factors involved in the success of post-core restoration. Seat design that is used in Prosthodontics Installation, Faculty of Dentistry, University of Padjadjaran, is in the contrary to minimal preparation design. The root fracture resistance of this design has not been proven yet. Purpose: The aim of this study was to evaluate the root fracture resistance of seat compare to non-seat design, with two different research methods: experimental laboratory and computer simulation with Finite Element Method (FEM). Method: The experimental laboratory investigation used 20 upper central incisors: 10 used seat design and 10 non-seats, with the cast posts cemented in the preparation. The specimens were tested by using Universal Testing Machine with compressive force until the root fracture. The FEM used 2D digital models: seat and non-seat design of maxillary central incisors using a finite element software. The distribution of internal stress caused by static loading 110N at 135° angle with longitudinal axis of the tooth was evaluated. Result: The results of the fracture strength test showed a significant difference (p = 0.05) between the non-seat group (852.27N ± 112.6N) and the seat group (495.78N ± 82.90N). The FEM showed a lower stress concentration in non-seat compare to seat group. This study proved that non-seat distributes stress better than seat design. Conclusion: It can be concluded that the FEM confirmed the result of the laboratory method. Stress concentration will cause fracture, therefore root fracture resistance in the non-seat design was higher than the seat design.